Aberrant neurovascular coupling in Leber’s hereditary optic neuropathy: Evidence from a multi-model MRI analysis - Ji, Yi; Wang, Ling; Ding, Hao; Tian, Qin; Fan, Ke; Shi, Dapeng; Yu, Chunshui; Qin, Wen (Frontiers in Neuroscience, 2023)
The study aimed to investigate the neurovascular coupling abnormalities in Leber’s hereditary optic neuropathy (LHON) and their associations with clinical manifestations. Twenty qualified acute Leber’s hereditary optic neuropathy (A-LHON, disease duration ≤ 1 year), 29 chronic Leber’s hereditary optic neuropathy (C-LHON, disease duration > 1 year), as well as 37 healthy controls (HCs) were recruited. The neurovascular coupling strength was quantified as the ratio between regional homogeneity (ReHo), which represents intrinsic neuronal activity and relative cerebral blood flow (CBF), representing microcirculatory blood supply. A one-way analysis of variance was used to compare intergroup differences in ReHo/CBF ratio with gender and age as co-variables. Pearson’s Correlation was used to clarify the association between ReHo, CBF, and neurovascular coupling strength. Furthermore, we applied linear and exponential non-linear regression models to explore the associations among ReHo/CBF, disease duration, and neuro-ophthalmological metrics. Compared with HCs, A_LHON, and C_LHON patients demonstrated a higher ReHo/CBF ratio than the HCs in the bilateral primary visual cortex (B_CAL), which was accompanied by reduced CBF while preserved ReHo. Besides, only C_LHON had a higher ReHo/CBF ratio and reduced CBF in the left middle temporal gyrus (L_MTG) and left sensorimotor cortex (L_SMC) than the HCs, which was accompanied by increased ReHo in L_MTG (p < 1.85e–3, Bonferroni correction). A-LHON and C-LHON showed a negative Pearson correlation between ReHo/CBF ratio and CBF in B_CAL, L_SMC, and L_MTG. Only C_LHON showed a weak positive correlation between ReHo/CBF ratio and ReHo in L_SMC and L_MTG (p < 0.05, uncorrected). Finally, disease duration was positively correlated with ReHo/CBF ratio of L_SMC (Exponential: Radj2 = 0.23, p = 8.66e–4, Bonferroni correction). No statistical correlation was found between ReHo/CBF ratio and neuro-ophthalmological metrics (p > 0.05, Bonferroni correction). Brain neurovascular “dyscoupling” within and outside the visual system might be an important neurological mechanism of LHON.